Studi Fenomenologi pada Kegiatan Yasinan Lanang dan Manakib Toriqoh Attijani di Buntet Pesantren - Rahman, Hanifah Aulia; Affandi, Akhmad (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This research aims to understand the religious meaning and the values of Islamic education within the tradition of Yasinan Lanang and Manakib Toriqoh Attijani, as well as to analyze how this activity strengthens the social and spiritual bonds among male participants in Mertapada Kulon Village, Buntet Pesantren. This study employs a qualitative-phenomenological approach. Data were collected through participant observation, in-depth interviews, and documentation, and subsequently analyzed using thematic analysis to explore the subjective experiences of the participants. The core findings indicate that this tradition serves not only as a routine ritual but also as an authentic space for spiritual and social education. It functions to foster inner peace, strengthen religious awareness, reinforce community solidarity through shared responsibilities, and act as a subtle form of social control based on Islamic moral values. The conclusion is that the Yasinan Lanang and Manakib tradition is a tangible manifestation of community-based non-formal religious education that effectively preserves and transmits Islamic values, while also highlighting the significant spiritual role of men within the community